Whole‐genome scanning for mapping determinacy in Pigeonpea (Cajanus spp.). Issue 5 (30th August 2012) - Mir, Reyazul Rouf; Saxena, Rachit K; Saxena, Kul Bhushan; Upadhyaya, Hari D; Kilian, Andrzej; Cook, Douglas R; Varshney, Rajeev K
Abstract Determinacy is an agronomically important trait in several crop species including pigeonpea. With an objective to investigate determinacy in pigeonpea, a set of 94 pigeonpea lines including 11 determinate (DT) and 83 indeterminate (IDT) lines were used for genotyping with DArT arrays (with 6144 features) and 768 SNP markers using GoldenGate assay. The polymorphism information content (PIC) for these markers varied from 0.02 to 0.50. Association analysis on marker genotyping and phenotyping data showed a significant association (P ≤ 0.01) of determinacy with 19 SNP and 6 DArT markers explaining 8.05–8.58% and 7.26–14.53% phenotypic variation, respectively. Clustering based on entire DArT and SNP markers could not discriminate DT lines from IDT lines; however, analysis with associated markers discriminated DT lines from the IDT lines. Marker–trait associations after validation may prove useful in marker‐assisted selection (MAS) involving the development of ideal DT genotypes for environments with moderate growth, tolerance to drought and water logging. This is the first report on mapping of determinacy trait as well as the first report on association mapping for any trait in pigeonpea.